Potential prognostic factors for cervical cancer patients undergoing radiotherapy at Charlotte Maxeke Johannesburg Academic Hospital: a retrospective analysis - Pule, Maleshwane Lettie (My University, 2014)
Introduction: Although cervical cancer can be prevented through known interventions it still remains a major cause of mortality in developing countries. Currently in South Africa there is little literature on cervical cancer radiotherapy treatment and its prognostic factors. Knowledge of prognostic factors helps in understanding the determinants of a disease better and optimize treatment strategies. The aim of this study was to determine overall survival rate and to investigate potential prognostic factors for cervical cancer in patients who underwent radiotherapy during the period of 1 January 2004 to 31 December 2006 at the Division of Radiation Oncology, Charlotte Maxeke Johannesburg Academic Hospital. Methods: This was a retrospective cohort study of 900 patients who were treated with radiotherapy between 1 January 2004 and 31 December 2006. Patient and treatment related data was obtained from the hospital treatment records. Follow-up was then censored as of 31st of December 2008. Subjects of this study had either mono-therapy or a combination of therapies: external beam radiotherapy, brachytherapy and chemotherapy. A Cox regression model was fitted to determine the prognostic and predictive factors of cervical cancer. Kaplan Meier methods were used to establish the effect of different socio-demographic and clinic-pathological factors on overall survival. The overall two year survival was also determined. Results: At 2 years post-treatment for each individual patient, 26 out of 900 patients had died, 281 were still alive and 593 lost to follow up leaving 307 patients available for analysis. The overall 2 year mortality rate was 45 per 1000 person years and highest in the period of 0-6 months. In the final model, completion of brachytherapy remained a significant predictor of survival (HR=0.04, 95% CI: 0.01-0.11, p<0.001) after adjusting for all other factors. Furthermore, HIV status was the only significant prognostic factor (HR=3.23, 95% CI: 1.04- 10, p=0.042). Patients who had brachytherapy treatment prescribed and completed the prescription were 96% less likely to die compared to those who didn’t complete it at any point in time, after adjusting for age and HIV status. Patients who were HIV positive were approximately three times more likely to die as compared to HIV negative patients at any point in time after adjusting for age and completed brachytherapy. The overall 2-year survival rate was 92% for this group of patients. Conclusion: Completion of the brachytherapy prescription was a significant predictor of treatment outcome, while the patient’s HIV status was also a significant prognostic factor for treatment. Patients who were HIV positive were three-times more likely to die compared to HIV negative patients. The overall 2-year survival rate was 92%, however, these results need to be interpreted with caution due to the large loss to follow-up in this patient population. Prospective clinical trials are recommended in the future to confirm the validity of the findings of this work in a representative patient population. In addition this work puts forward some suggestions to optimize treatment of cervical cancer patients in typical university teaching public health centres in South Africa.
Keywords: Uterine Cervical Neoplasms--radiotherapy